Sexual and reproductive health among adolescent girls and young women in Mombasa, Kenya. Issue 1 (1st January 2020) - Wilson, Andrea; Musyoki, Helgar; Avery, Lisa; Cheuk, Eve; Gichangi, Peter; Bhattacharjee, Parinita; Musimbe, Janet; Leung, Stella; Blanchard, James; Moses, Stephen; Mishra, Sharmistha; Becker, Marissa; et al.
ABSTRACT: This secondary data analysis of a cross-sectional survey conducted in Mombasa, Kenya characterises sexual and reproductive health (SRH) indicators among adolescent girls and young women (AGYW) engaged in casual and transactional sexual relationships as well as sex work. It describes the association between awareness of local HIV programmes and SRH services uptake for AGYW engaged in sex work. Thirty-eight percent of the participants reported a history of pregnancy. Among participants not trying to get pregnant, 27% stated that they were not currently using any form of contraception. Of the participants who had an abortion, 59% were completed under unsafe conditions. For AGYW engaged in sex work, awareness of local HIV prevention programmes was associated with increased STI testing within the last year (29%) as well as at least one HIV test (99%) compared to those who were not aware of local programming (18% and 92%, respectively); however, only 26% of participants engaged in sex work had heard of local HIV prevention programmes. There were no associations between awareness of local HIV programming and rates of dual contraception use, safe abortion, most recent birth attended by a skilled health professional or testing for HIV during pregnancy. Our study found high need for SRH services, particularly, access to contraception and safe abortion. Continued efforts are required to improve access to the full spectrum of SRH interventions, including family planning services and access to safe abortion in addition to HIV prevention to promote health equity.